Comparison of prasugrel and clopidogrel in patients with non-cardioembolic ischaemic stroke: a phase 3, randomised, non-inferiority trial (PRASTRO-I). Issue 3 (March 2019) - Ogawa, Akira; Toyoda, Kazunori; Kitagawa, Kazuo; Kitazono, Takanari; Nagao, Takehiko; Yamagami, Hiroshi; Uchiyama, Shinichiro; Tanahashi, Norio; Matsumoto, Masayasu; Minematsu, Kazuo; Nagata, Izumi; Nishikawa, Masakatsu; et al.
Summary: Background: The effect of prasugrel in terms of the prevention of recurrence of ischaemic stroke is unknown. We investigated the non-inferiority of prasugrel to clopidogrel for prevention of ischaemic stroke, myocardial infarction, and death from other vascular causes in Japanese patients with non-cardioembolic stroke. Methods: In this phase 3 randomised, double-blind, non-inferiority trial, patients aged 20–74 years who had had a non-cardioembolic stroke in the previous 1–26 weeks were recruited from 224 hospitals in Japan. Eligible patients were randomly assigned (1:1) to receive prasugrel (3·75 mg/day) or clopidogrel (75 mg/day) orally for 96–104 weeks. Randomisation was stratified according to stroke subtype. The randomisation schedule was generated by an independent statistician who created a computer-generated random number sequence. Patients, investigators, and the funder were masked to treatment allocation. The primary endpoint was combined incidence of ischaemic stroke (fatal and non-fatal), myocardial infarction (fatal and non-fatal), and death from other vascular causes in the intention-to-treat population. The safety endpoint was incidence of bleeding events, comprising life-threatening bleeding, major bleeding, and clinically relevant bleeding. The safety analysis was done in the population excluding trial patients with serious Good Clinical Practice violations, and those who had not taken the trial drug. The predefined non-inferiority margin was an upper 95% CI limit for the risk ratio (RR) of 1·35. The trial was registered with the Japan Pharmaceutical Information Center (JapicCTI-111582). Findings: Patients were recruited between Sept 1, 2011, and June 12, 2015. 3747 patients (797 [21%] women) were enrolled, with a mean age of 62·1 (SD 8·5) years. 3753 patients were randomly assigned to treatment and, of these patients, 1885 in the prasugrel group and 1862 in the clopidogrel group were confirmed to have taken the trial drug at least once, and six patients withdrew from the trial before administration of the trial drug. Thus, a total of 3747 patients were included in the full analysis set. 73 (4%) of 1885 patients in the prasugrel group and 69 (4%) of 1862 patients in the clopidogrel group reached the primary endpoint (RR 1·05, 95% CI 0·76–1·44). The incidence of bleeding events was not significantly different between treatment groups; life-threatening bleeding was observed in 18 (1%) patients in the prasugrel group and 23 (1%) patients in the clopidogrel group (RR 0·77, 0·41–1·42). Interpretation: The non-inferiority of prasugrel to clopidogrel for the prevention of ischaemic stroke, myocardial infarction, and death from other vascular causes was not confirmed in Japanese patients with non-cardioembolic stroke. No safety concerns were identified. Funding: Daiichi Sankyo.